A Conceptual Framework for Online Authentic Learning to Support Knowledge Construction Among Undergraduates - Hua Lau, Ung; Tasir, Zaidatun (International Journal of Engineering and Technology, 2018)
The paper presents a conceptual framework of studentsâ€™ knowledge construction through online authentic learning environment in learning inferential statistics that enhance studentsâ€™ performance and knowledge retention. The online learning environment is proposed based on situated learning theory and social learning theory as an approach for promoting knowledge construction of the students. An authentic task will serve as the precursor to encourage social interaction among students, teachers and more experienced experts in the process. The social interaction afforded by online learning environment facilitate studentsâ€™ knowledge construction, leading to studentsâ€™ performance and knowledge retention.Â Â Â